2023
DOI: 10.1093/treephys/tpad001
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal, physiological and transcriptomic dynamics of wild jujube seedlings under saline conditions

Abstract: Soil salinity is a major constraint limiting jujube production in China. Wild jujube (Ziziphus jujuba var. spinosa (Bunge) Hu ex H. F. Chow) is widely used as the rootstock of jujube (Z. jujuba) to overcome the saline conditions. To understand the adaptive mechanism in wild jujube under saline conditions, we combined spatiotemporal and physiological assessments with transcriptomic analysis on wild jujube seedlings undergoing various salt treatments. These salt treatments showed dose and duration effects on bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Among the most common effects of salinity on plants, growth reduction is a major constraint in plant production that results in yield losses [ [1] , [2] , [64] , [67] ]. Our results revealed that salinity had deleterious effects on maize growth parameters such as PH, CL, RT, RDW, SDW, and GW compared to those which were not subjected to salinity ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the most common effects of salinity on plants, growth reduction is a major constraint in plant production that results in yield losses [ [1] , [2] , [64] , [67] ]. Our results revealed that salinity had deleterious effects on maize growth parameters such as PH, CL, RT, RDW, SDW, and GW compared to those which were not subjected to salinity ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Salinity affects plant growth and physiological activity by imposing osmotic stress and hampers nutrient uptake [ [2] , [64] , [67] ]. In this work, ionic uptake and built-up in the leaves and roots of maize plants have gained special focus.…”
Section: Discussionmentioning
confidence: 99%
“…Salinity-induced reduction in water loss through transpiration and reduced stomatal opening suggests its plant adaptation mechanism under stress conditions. Salt stress leads to stomatal closure to conserve water, altering photosynthetic efficiency [53,54] and a recent study discussed the genetic basis of plants' adaptive mechanisms to decrease water loss under salt stress [55].…”
Section: Discussionmentioning
confidence: 99%
“…Statistix 10.0 (Analytical Software, Statistix; Tallahassee, FL, USA, 1985–2003) was used to statistically analyze the data using the analysis of variance technique, and treatment means were compared at ( P ≤ 0.05) by utilizing the least significant difference (LSD) 57 Graphical representation was done with Sigma Plot 10.0, and the correlation matrix of data was done with Statistix 10. A polar heat-map with a dendrogram was made by using OriginPro-2022 and supplemented with various analyses 4 , 58 .…”
Section: Methodsmentioning
confidence: 99%